A cross-cultural analysis of perceived product quality, perceived risk and purchase intention in e-commerce platforms. Issue 1 (13th November 2019) - Rosillo-Díaz, Elena; Blanco-Encomienda, Francisco Javier; Crespo-Almendros, Esmeralda
Abstract : Purpose: While there have always been cultural differences between countries and between individuals, the virtualisation of markets is rendering the impact of these differences even more salient. There is clear evidence that cultural dimensions are relevant in the adoption and use of e-commerce. The purpose of this paper is to analyse the significant effects of individual cultural dimensions on perceived product quality, perceived risk and purchase intention in e-commerce platforms. Design/methodology/approach: A questionnaire was developed to serve as a tool of measurement. A confirmatory factor analysis was conducted to examine whether all the indicators for the constructs are reliable. A multiple regression analysis was carried out to test the hypotheses. Findings: The results reveal that, in the case of e-commerce platforms, the cultural dimensions uncertainty-avoidance and collectivism exert a significant influence on perceived product quality, perceived risk and purchase intention. Research limitations/implications: The present study is based on real well-known e-commerce platforms which could have influenced the responses of the sample due to potential past experiences of use. An experimental design based on fictitious platforms could offer more objective findings. Practical implications: This research contributes to the understanding of e-commerce and the behaviour of consumers during online purchasing, taking into account the cultural differences that may exist between them. Originality/value: The literature on individual cultural dimensions – that is, non-national cases – and the variables analysed in the present study suffers from great limitations. This study complements a growing interest in analysing the individual cultural dimensions and their effects on the sphere of e-commerce, specifically on perceived product quality, purchase intention and perceived risk during browsing, measured in terms of the six types of risk prevalent in e-commerce platforms.